Libraries and public perception a comparative analysis of the European press - Galluzzi, Anna (Oxford, UK Chandos Publishing, 2014)
What is the future of libraries? This question is frequently posed, with widespread research into the social and economic impact of libraries. Newspapers play an important role in forming public perceptions, but how do newspapers present libraries, their past, present and future? Nobody has yet taken the press to task on the quantity and quality of articles on libraries, however Libraries and Public Perception does just this, through comparative textual analysis of newspapers in Europe. After a comprehensive and useful introductory chapter, the book consists of the following five chapters: Won.
Keywords: Libraries -- Public opinion; Libraries and mass media; Library use studies; Library users -- Attitudes